Stunting Prevention Efforts in Paccinongang Village Through Germas Panting (Paccinongang Community Movement to Overcome Stunting) - Ansyar, Dian Ihwana; Kurniati, Yessy; Rahma, Andi Anugrah; Khaerah, Ummul; Munir, Miftahul Jannah (Universitas Islam Negeri Alauddin Makassar, 2025)
Nutrition remains a major public health issue in Indonesia, significantly affecting the quality of human resources. One persistent nutritional problem is stunting, which continues to impact many communities, including Pacciongang Hamlet, where data showed a stunting prevalence of 11.1%. The program included problem identification, development of a problem-solving framework, and implementation through a series of activities: pre-test, health education, post-test, and practical training. One key intervention was a demonstration of preparing complementary food using local ingredients—specifically, Moringa leaves processed into nutritious pudding. Moringa was chosen due to its high protein content and availability in the village. To evaluate the effectiveness of the intervention, pre- and post-tests were conducted to assess participants' knowledge on stunting, exclusive breastfeeding, and the benefits of Moringa. Data were analyzed using the Wilcoxon test. The results showed a significant increase in participants' understanding, with a p-value < 0.05, indicating a meaningful difference in knowledge before and after the counseling sessions. Additionally, the demonstration session successfully empowered participants to prepare and serve Moringa pudding following the given recipe. This initiative not only increased awareness of stunting prevention but also provided a practical solution using affordable and accessible local resources. In conclusion, the health education and training activities were effective in enhancing community knowledge and skills related to child nutrition and stunting prevention. This community-based approach highlights the importance of local resource utilization and participatory education in improving public health outcomes.